Penerapan Manajemen Kewirausahaan dalam Aspek Kreativitas dan Inovasi di SMK PGRI 2 Sidoarjo - Satunggale Kurniawan (Indo-MathEdu Intellectuals Journal, 2023)
The ability of a school principal who has an entrepreneurial spirit in terms of innovation can greatly determine the success of the school he leads because within the school principal is able and able to respond to the needs or desires and expectations of the community as an educational service for their children. Therefore, if you want to be successful in leading a school, be a creative and innovative individual in terms of realizing the creative potential that you can have in the form of quality innovation. The process of implementing entrepreneurial management at SMK PGRI 2 Sidoarjo, goes according to predetermined programs. Among them in carrying out entrepreneurship, schools always prepare themselves with Entrepreneurial Planning at SMK PGRI 2 Sidoarjo is an activity to think in advance about things that must be done regarding students at school, both since students will enter school, while at school, and they will graduate from school. What is planned is the things that must be done with regard to the acceptance of students until the graduation of students. School policies identify activities that can be used to achieve the target or goal of student success. In terms of this research approach is qualitative research, in terms of this research, there are problems that can be raised are activities related to giving ideas or ideas in an entrepreneurial spirit carried out by the principal of SMK PGRI 2 Sidoarjo, the result is that the Principal of SMK PGRI 2 Sidoarjo As a knowledge leader always prioritizing the role of the principal as a knowledge leader is a step forward in directing changes in the school's organizational culture. Increasing Creativity is carried out through: a climate of mutual trust and shared commitment; honest and open communication; creative problem solving; and flexible school management processes